Muscle stiffness as a cause of reduced muscle volume - a reliability study - McEarl, Amanda L. (My University, 2014)
A leading cause of impairment in elderly individuals is sarcopenia, the progressive deterioration of muscle size and strength, which ultimately limits muscle functionality. The loss of muscular strength is directly correlated with increased mortality, hypertension, metabolic syndrome, and diabetes. This corresponds with limitations to activities of daily living, therefore further restricting the individual’s independence. The purpose of our study is to test the reliability of our methods for measuring muscle volume, stiffness, and strength for future sarcopenia research. We have evidence proving the validity of ultrasound and elastography techniques to measure muscle volume and stiffness. We have targeted the medial and lateral gastrocnemius muscles in 6 young adults aged 20-30 years old. Measurements will be taken along the longitudinal axis via ultrasound to determine muscular length. Muscular area will be calculated by taking 5 cross-sectional ultrasound measurements across the muscle. These measurements together will be used to calculate muscular volume, while muscular stiffness will be measured using ultrasound elastography. Isokinetic and Isometric strength tests will be performed on the Humac dynamometer and will represent the maximum muscular strength of each subject. A Bland-Altman plot and regression analysis will be performed for each method comparing data from the first testing session against the second to verify reliability. A regression analysis will also be performed to determine the relationship between muscle volume, strength and stiffness to determine if there is a correlation in a young population.
Keywords: Sarcopenia; Elastography; Ultrasounds; Muscle volume; Muscular strength; Muscle stiffness